2013
DOI: 10.1007/s11427-013-4536-7
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of nerve root sheaths for sacral extradural spinal meningeal cysts with spinal nerve root fibers

Abstract: This study analyzed the clinical characteristics and outcomes of sacral extradural spinal meningeal cysts with spinal nerve root fibers treated by reconstruction of the nerve root sheaths. The relationships between the cysts and spinal nerve root fibers were examined microscopically, the cysts were partially excised, and the defects were oversewn to reconstruct the nerve root sheaths. The Improved Japanese Orthopedic Association (IJOA) scoring system was used to evaluate preoperative and postoperative neurolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 19 publications
2
28
1
Order By: Relevance
“…Sun et al reported that nerve root L5 is frequently involved [24]. In our study, TCs and EMG abnormalities were also frequently detected in the L5 myotomes.…”
Section: Locationsupporting
confidence: 75%
See 4 more Smart Citations
“…Sun et al reported that nerve root L5 is frequently involved [24]. In our study, TCs and EMG abnormalities were also frequently detected in the L5 myotomes.…”
Section: Locationsupporting
confidence: 75%
“…In aneurysms, years of increased pressure force a weakened vessel wall to enlarge. Similarly, nerve root dilation may require a long period of increased hydrostatic pressure in the spinal canal [2,19,[21][22][23][24].…”
Section: Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations